Can Ethiopia feed itself by 2050? Estimating cereal self-sufficiency to 2050 - Tesfaye, Kindie; Ittersum, Martin K. van; Wiebe, Keith D.; Boogaard, Hendrik L.; Radeny, Maren A.O.; Solomon, Dawit (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2018)
Producing adequate food to meet global demand by 2050 is widely recognized as a major challenge, particularly for sub-Saharan Africa (SSA) (Godfray et al. 2010; Alexandratos and Bruinsma 2012; van Ittersum et al. 2016). Increased price volatility of major food crops (Koning et al. 2008; Lagi et al. 2011), an abrupt surge in land area devoted to crop production in recent years (Grassini et al. 2013) and extensive labour force mobilization (NEPAD 2013) reflect the powerful forces underpinning this challenge to increase production. The 2008 price spikes triggered the Food and Agriculture Organization of the United Nations (FAO) and the World Food Programme (WFP) to issue warnings, noting the 60–70 percent increase in food production by 2050 that will be needed to meet the escalating food demand for the expected 9.7 billion global population. In this policy brief we focus on the feasibility to meet such increase by 2050 with scenarios of population increase and dietary changes under current climate conditions. Current climate variability is very high in sub-Saharan Africa causing significant yield variations across years (e.g., Shiferaw et al. 2014; www.yieldgap.org). Climate change will further add to the food production challenge (Porter et al. 2014; Vermeulen et al. 2012; McKersie 2015). Smallholder farmers will need to adapt to a changing climate while at the same time they are expected to increase production in such way that it has a minimum effect on the drivers of climate change, i.e. mitigating greenhouse gas emissions.